Aerogel composite modified heat-resistant and heat-insulating asphalt material as well as preparation method and application of aerogel composite modified heat-resistant and heat-insulating asphalt material

By adding aerogel composite modifiers to the asphalt pavement, the problem that asphalt pavement cannot effectively regulate the temperature in areas with large temperature differences is solved, and the effect of slowing down the pavement temperature change speed, extending service life and improving durability is achieved.

CN119391196APending Publication Date: 2025-02-07CHINA RAILWAY URBAN DEVELOPMENT INVESTMENT GROUP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411484746.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing asphalt pavement cannot effectively control the pavement temperature in areas with large temperature differences, and its service life and durability are insufficient, and it faces diseases such as deformation, packaging, and ruts.

Method used

Aerogel composite modifiers, including SiO2 aerogel powder, carbon nanotubes and hollow glass microbeads, are incorporated into asphalt. By preparing aerogel composite modified thermal insulation asphalt materials, the temperature rise of pavement structure is slowed down. and cooling rate.

Benefits of technology

It effectively slows down the temperature change speed of the pavement structure, extends the service life of the pavement, improves durability, and reduces diseases caused by excessive temperature difference.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005098438210000111
    Figure BDA0005098438210000111
  • Figure BDA0005098438210000121
    Figure BDA0005098438210000121
Patent Text Reader

Abstract

The invention belongs to the technical field of road building materials, and relates to an aerogel composite modified heat-resistant thermal-insulation asphalt material which comprises the following components in parts by mass: 8-15 parts of SiO2 aerogel powder; 1-4 parts of a carbon nanotube; 1-3 parts of hollow glass beads; 80 to 85 parts of asphalt; the SiO2 aerogel powder, the carbon nanotubes and the hollow glass beads form an aerogel composite modifier; in the aerogel composite modified heat-resistant thermal-insulation asphalt material, the doping amount of the aerogel composite modifier is 15%-20%. The invention further discloses a preparation method and application of the aerogel composite modifier, the aerogel composite modifier composed of the SiO2 aerogel powder, the carbon nanotubes and the hollow glass beads is used in the asphalt pavement, the durability of the pavement can be improved, and the tolerance of the pavement structure to extreme air temperature can also be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of road construction materials, and specifically relates to an aerogel composite modified heat-resistant and temperature-insulating asphalt material and a preparation method and application thereof. Background Art

[0002] Asphalt pavement has become the main structural form of high-grade pavement due to its smooth and continuous surface, high driving comfort, easy construction and maintenance, and early opening to traffic. Asphalt is the most widely used and largest pavement material in current highway design. It is very sensitive to temperature changes in the working environment. In high temperature environments, deformation, bulging, rutting and other defects of varying degrees are very likely to occur. In low temperature environments, cracks and other pavement defects are prone to occur. Not only does it increase the difficulty of daily pavement maintenance and shorten the service life of the road, but it also poses a huge challenge to the comfort and safety of highway driving.

[0003] Regarding the construction of pavement in areas with large temperature differences, it can be divided into passive temperature control technology and active temperature control technology according to different types of technology. Passive temperature control technology often improves the stability of pavement materials in high and low temperature environments by modifying pavement materials. This method improves the performance of the pavement, but it cannot completely solve the problem of pavement performance. It only delays the occurrence of pavement diseases. Various diseases will still occur in long-term extreme high and low temperatures and environments with drastic temperature changes. Active temperature control technology is divided into two main categories: one is phase change technology, which adds phase change materials to the pavement to change the pavement temperature. Although this method can effectively reduce the pavement temperature, most of the phase change materials used in the pavement will reduce the pavement performance and face the defect of attenuation of temperature control ability; the other is insulation technology, which uses a certain material to prevent or delay a large amount of heat from flowing into and out of the pavement structure in a short period of time, thereby achieving the effect of temperature control and temperature regulation. The main path is pavement coating technology, but this type of technology often faces the defects of limited insulation effect and insufficient durability due to problems such as the thickness of the coating itself.

[0004] In short, the current asphalt pavement construction in areas with large temperature differences faces many defects such as the inability to effectively control the pavement temperature, insufficient service life and durability, etc. Therefore, there is an urgent need for a modified asphalt material that can delay the temperature rise and fall rate of the pavement structure in areas with large temperature differences through thermal insulation. Summary of the invention

[0005] The purpose of the present invention is to provide an aerogel composite modified heat-resistant and temperature-insulating asphalt material, a preparation method and an application thereof, so as to solve the problems that the existing asphalt pavement cannot effectively regulate the pavement temperature and has insufficient service life and durability.

[0006] The present invention is achieved through the following technical solutions:

[0007] An aerogel composite modified heat-resistant and heat-insulating asphalt material, comprising the following components by weight:

[0008] 8-15 parts of SiO2 aerogel powder; 1-4 parts of carbon nanotubes; 1-3 parts of hollow glass microspheres; 80-85 parts of asphalt;

[0009] SiO2 aerogel powder, carbon nanotubes and hollow glass microspheres constitute an aerogel composite modifier;

[0010] In the aerogel composite modified heat-resistant and temperature-insulating asphalt material, the content of the aerogel composite modifier is 15%-20%.

[0011] Furthermore, the carbon nanotubes are multi-walled carbon nanotubes.

[0012] Furthermore, the particle size of SiO2 aerogel powder ranges from 0.1 to 5 mm, and the specific surface area is 800 to 1000 m2 / g.

[0013] Furthermore, the carbon nanotubes have a diameter of 12-200 nm and a length of 0.5-15 μm.

[0014] The present invention also discloses a method for preparing the aerogel composite modified heat-resistant and temperature-insulating asphalt material, comprising the following steps:

[0015] (1) mixing SiO2 aerogel powder, carbon nanotubes and an organic solvent, and adding hollow glass microspheres during the stirring process to obtain a mixed solution;

[0016] (2) drying the mixed solution to obtain a blend of aerogel and carbon nanotubes;

[0017] (3) subjecting the blend to high temperature treatment to obtain a dry mixed material;

[0018] (4) granulating and grinding the dry mixed material to obtain an aerogel composite modifier;

[0019] (5) Heating the asphalt and performing shear stirring, and then mixing the emulsified asphalt with the aerogel composite modifier to obtain an aerogel composite modified heat-resistant and temperature-insulating asphalt material.

[0020] Furthermore, in step (1), the stirring temperature is 20-40° C., the stirring time is 30-45 min, and the stirring speed is 1000-3000 rpm.

[0021] Further, in step (2), the mixed solution is dried, specifically:

[0022] The mixed solution is placed and evaporated at low temperature, the placing time is 24±1h, and the low temperature evaporation is carried out at 50°C for 6±1h.

[0023] Furthermore, step (4) specifically comprises: granulating the dry mixed material to obtain a material with an initial particle size;

[0024] Grinding the initial particle size material to obtain an aerogel composite modifier;

[0025] The particle size of the initial particle size material is in the millimeter order; the particle size of the aerogel composite modifier is in the micron order.

[0026] Furthermore, in step (5), the emulsified asphalt and the aerogel composite modifier are mixed and stirred at a stirring speed of 300 to 500 rpm, a stirring temperature of 140 to 160° C., and a stirring time of 30 to 45 min.

[0027] The invention also discloses the application of the aerogel composite modified heat-resistant and temperature-insulating asphalt material as a heat-insulating layer in an asphalt pavement, which is used for the upper layer of an asphalt pavement structure.

[0028] Compared with the prior art, the present invention has the following beneficial technical effects:

[0029] The present invention discloses an aerogel composite modified heat-resistant and heat-insulating asphalt material, comprising 8-15 parts of SiO2 aerogel powder; 1-4 parts of carbon nanotubes; 1-3 parts of hollow glass microspheres; and 80-85 parts of asphalt. The prepared aerogel composite modifier is fully mixed with hot asphalt and used in asphalt mixture of the road surface. The main component of the modifier is aerogel, which has excellent thermal insulation performance. It can effectively slow down the heating and cooling speed of the road surface structure when used in the asphalt mixture, and change the temperature curve of the road surface structure in the area with large temperature difference by delaying the heating and cooling speed, thereby reducing the road surface diseases caused by excessive temperature difference and rapid temperature change. However, materials such as aerogels themselves have the disadvantages of being too hard and too brittle, which easily leads to a decrease in the crack resistance of the asphalt surface layer in practical applications. Therefore, hollow glass microspheres and carbon nanotubes are added to improve the overall toughness of the modified asphalt mixture. Aerogel composite modifiers composed of SiO2 aerogel powder, carbon nanotubes and hollow glass beads are used in asphalt pavements, which can not only improve the durability of the pavement, but also enhance the pavement structure's tolerance to extreme temperatures.

[0030] The invention discloses a method for preparing an aerogel composite modified heat-resistant and heat-insulating asphalt material, wherein SiO2 aerogel powder is first blended with carbon nanotubes, and then hollow glass microspheres are added; the mixed solution is dried to precipitate excess ethanol and obtain a blend of aerogel and carbon nanotubes; the dried mixed material is granulated to obtain a small-sized particle material, and then ground to further refine the particle size to obtain an aerogel composite modifier; controlling the particle size can make the modifier particles better dispersed in the asphalt, and the effect will be better; the asphalt is heated and sheared and stirred, and the aerogel composite modifier is evenly poured into the asphalt in batches, and stirred evenly to obtain the aerogel composite modified heat-resistant and heat-insulating asphalt material. The preparation process is simple, does not require high-end equipment, and has low cost.

[0031] The present invention also discloses the application of the aerogel composite modified heat-resistant and heat-insulating asphalt material, which is used for the upper layer of the asphalt pavement structure, so that the temperature change rate of the pavement structure under high and low temperature environments is greatly reduced, and the heating and cooling rates inside the pavement structure are slowed down, thereby reducing the heating and cooling amplitudes under drastic temperature changes in areas with large temperature differences. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical scheme and advantages of the present invention clearer, the following is further described in detail with reference to the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, rather than all the embodiments.

[0033] The detailed description of the embodiments of the present invention provided below is not intended to limit the scope of the invention claimed for protection, but merely represents a selected embodiment of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.

[0034] The features and performances of the present invention are further described in detail below in conjunction with the embodiments.

[0035] Example 1

[0036] Example 1 provides an aerogel composite modified heat-insulating asphalt material, which includes the following raw materials by weight: 15 parts of SiO2 aerogel powder, 2 parts of carbon nanotubes, 3 parts of hollow glass microspheres, and 80 parts of asphalt, wherein the carbon nanotubes are multi-walled structures with a tube diameter of 12-200nm and a length of 0.5-15μm. The hollow glass microspheres are 30 meshes.

[0037] Preparation method:

[0038] (1) SiO2 aerogel powder and carbon nanotubes are mixed in anhydrous ethanol, the mixed solution is added to a stirrer for stirring, and hollow glass microspheres are added during the stirring process. The stirring temperature is 20°C, the stirring time is 45 minutes, and the stirring speed is 2000 rpm.

[0039] (2) The stirred solution was placed and evaporated at low temperature to precipitate excess ethanol, thereby obtaining a blend of aerogel, carbon nanotubes and hollow glass microspheres. The placement time was 24 hours and the evaporation time was 6 hours at 50°C.

[0040] (3) The dry mixed material was added into an extrusion granulator for granulation, and the particle size was 1 mm.

[0041] (4) The obtained granules were placed in a ball mill for grinding at a speed of 600 rpm for 1 hour, and finally an aerogel composite modifier with a particle size of 60 μm was obtained.

[0042] (5) The asphalt is heated and stirred at a stirring speed of 500 rpm and a stirring temperature of 160° C. for 40 min using a high-speed emulsifying shearing machine, and the aerogel composite modifier is evenly poured into the emulsified asphalt twice to obtain an aerogel composite modified heat-resistant and heat-insulating asphalt material.

[0043] Example 2

[0044] Example 2 provides an aerogel composite modified heat-insulating asphalt material, which includes the following raw materials by weight: 11.5 parts of SiO2 aerogel powder, 1.5 parts of carbon nanotubes, 2 parts of hollow glass microspheres, and 85 parts of asphalt, wherein the carbon nanotubes are multi-walled structures with a tube diameter of 12-200nm and a length of 0.5-15μm. The hollow glass microspheres are 30 meshes.

[0045] Preparation method:

[0046] (1) SiO2 aerogel powder and carbon nanotubes are mixed in anhydrous ethanol, the mixed solution is added to a stirrer for stirring, and hollow glass microspheres are added during the stirring process. The stirring temperature is 40°C, the stirring time is 30 minutes, and the stirring speed is 2000 rpm.

[0047] (2) The stirred solution was placed and evaporated at low temperature to precipitate excess ethanol, thereby obtaining a blend of aerogel, carbon nanotubes and hollow glass microspheres. The placement time was 24 hours and the evaporation time was 6 hours at 50°C.

[0048] (3) The dry mixed material was added into an extrusion granulator for granulation, and the particle size was 1 mm.

[0049] (4) The obtained granules were placed in a ball mill for grinding at a speed of 600 rpm for 1 hour, and finally an aerogel composite modifier with a particle size of 60 μm was obtained.

[0050] (5) The asphalt is heated and stirred at a stirring speed of 500 rpm and a stirring temperature of 160° C. for 40 min using a high-speed emulsifying shearing machine, and the aerogel composite modifier is evenly poured into the emulsified asphalt twice to obtain an aerogel composite modified heat-resistant and heat-insulating asphalt material.

[0051] Example 3

[0052] Example 3 provides a new type of road aerogel insulation layer for areas with large temperature differences, which includes the following raw materials by weight: 8 parts of SiO2 aerogel powder, 4 parts of carbon nanotubes, 3 parts of hollow glass microspheres, and 85 parts of asphalt. The carbon nanotubes are multi-walled structures with a tube diameter of 12-200nm and a length of 0.5-15μm. The hollow glass microspheres are 30 meshes.

[0053] Preparation method:

[0054] (1) SiO2 aerogel powder and carbon nanotubes are mixed in anhydrous ethanol, the mixed solution is added to a stirrer for stirring, and hollow glass microspheres are added during the stirring process. The stirring temperature is 20°C, the stirring time is 45 minutes, and the stirring speed is 2000 rpm.

[0055] (2) The stirred solution was placed and evaporated at low temperature to precipitate excess ethanol, thereby obtaining a blend of aerogel, carbon nanotubes and hollow glass microspheres. The placement time was 25 hours, and the evaporation time was 5 hours at 50°C.

[0056] (3) The dry mixed material was added into an extrusion granulator for granulation, and the particle size was 1 mm.

[0057] (4) The obtained granules were placed in a ball mill for grinding at a speed of 600 rpm for 1 hour, and finally an aerogel composite modifier with a particle size of 60 μm was obtained.

[0058] (5) The asphalt is heated and stirred at a stirring speed of 500 rpm and a stirring temperature of 160° C. for 40 min using a high-speed emulsifying shearing machine, and the aerogel composite modifier is evenly poured into the emulsified asphalt in batches to obtain an aerogel composite modified heat-resistant and heat-insulating asphalt material.

[0059] Example 4

[0060] Example 4 provides a new type of road aerogel insulation layer for areas with large temperature differences, which includes the following raw materials by weight: 13 parts of SiO2 aerogel powder, 1 part of carbon nanotubes, 1 part of hollow glass microspheres, and 85 parts of asphalt. The carbon nanotubes are multi-walled structures with a tube diameter of 12-200nm and a length of 0.5-15μm. The hollow glass microspheres are 30 meshes.

[0061] Preparation method:

[0062] (1) SiO2 aerogel powder and carbon nanotubes are mixed in anhydrous ethanol, the mixed solution is added to a stirrer for stirring, and hollow glass microspheres are added during the stirring process. The stirring temperature is 20°C, the stirring time is 45 minutes, and the stirring speed is 2000 rpm.

[0063] (2) The stirred solution was placed and evaporated at low temperature to precipitate excess ethanol, thereby obtaining a blend of aerogel, carbon nanotubes and hollow glass microspheres. The placement time was 25 hours, and the evaporation time was 5 hours at 50°C.

[0064] (3) The dry mixed material was added into an extrusion granulator for granulation, and the particle size was 1 mm.

[0065] (4) The obtained granules were placed in a ball mill for grinding at a speed of 600 rpm for 1 hour, and finally an aerogel composite modifier with a particle size of 60 μm was obtained.

[0066] (5) The asphalt is heated and stirred at a stirring speed of 500 rpm and a stirring temperature of 160° C. for 40 min using a high-speed emulsifying shearing machine, and the aerogel composite modifier is evenly poured into the emulsified asphalt in batches to obtain an aerogel composite modified heat-resistant and heat-insulating asphalt material.

[0067] Example 5

[0068] Example 5 provides a new type of road aerogel insulation layer for areas with large temperature differences, which includes the following raw materials by weight: 13 parts of SiO2 aerogel powder, 1 part of carbon nanotubes, 1 part of hollow glass microspheres, and 85 parts of asphalt. The carbon nanotubes are multi-walled structures with a tube diameter of 12-200nm and a length of 0.5-15μm. The hollow glass microspheres are 30 meshes.

[0069] Preparation method:

[0070] (1) SiO2 aerogel powder and carbon nanotubes are mixed in anhydrous ethanol, the mixed solution is added to a stirrer for stirring, and hollow glass microspheres are added during the stirring process. The stirring temperature is 20°C, the stirring time is 45 minutes, and the stirring speed is 2000 rpm.

[0071] (2) The stirred solution was placed and evaporated at low temperature to precipitate excess ethanol, thereby obtaining a blend of aerogel, carbon nanotubes and hollow glass microspheres. The placement time was 24 hours and the evaporation time was 6 hours at 50°C.

[0072] (3) The dry mixed material was added into an extrusion granulator for granulation, and the particle size was 1 mm.

[0073] (4) The obtained granules were placed in a ball mill for grinding at a speed of 600 rpm for 1 hour, and finally an aerogel composite modifier with a particle size of 60 μm was obtained.

[0074] (5) The asphalt is heated and stirred at a stirring speed of 500 rpm and a stirring temperature of 160° C. for 40 min using a high-speed emulsifying shearing machine, and the aerogel composite modifier is evenly poured into the emulsified asphalt in batches to obtain an aerogel composite modified heat-resistant and heat-insulating asphalt material.

[0075] Example 6

[0076] Example 6 provides a new type of road aerogel insulation layer for areas with large temperature differences, which includes the following raw materials by weight: 13 parts of SiO2 aerogel powder, 1 part of carbon nanotubes, 1 part of hollow glass microspheres, and 85 parts of asphalt. The carbon nanotubes are multi-walled structures with a tube diameter of 12-200nm and a length of 0.5-15μm. The hollow glass microspheres are 30 meshes.

[0077] Preparation method:

[0078] (1) SiO2 aerogel powder and carbon nanotubes were mixed in anhydrous ethanol, the mixed solution was added into a stirrer for stirring, and hollow glass microspheres were added during the stirring process. The stirring temperature was 20°C, the stirring time was 45 minutes, and the stirring speed was 3000 rpm.

[0079] (2) The stirred solution was placed and evaporated at low temperature to precipitate excess ethanol, thereby obtaining a blend of aerogel, carbon nanotubes and hollow glass microspheres. The placement time was 24 hours and the evaporation time was 6 hours at 50°C.

[0080] (3) The dry mixed material was added into an extrusion granulator for granulation, and the particle size was 1 mm.

[0081] (4) The obtained granules were placed in a ball mill for grinding at a speed of 600 rpm for 1 hour, and finally an aerogel composite modifier with a particle size of 60 μm was obtained.

[0082] (5) The asphalt is heated and stirred at a stirring speed of 500 rpm and a stirring temperature of 160° C. for 40 min using a high-speed emulsifying shearing machine, and the aerogel composite modifier is evenly poured into the emulsified asphalt in batches to obtain an aerogel composite modified heat-resistant and heat-insulating asphalt material.

[0083] Example 7

[0084] Example 7 provides a new type of road aerogel insulation layer for areas with large temperature differences, which includes the following raw materials by weight: 13 parts of SiO2 aerogel powder, 1 part of carbon nanotubes, 1 part of hollow glass microspheres, and 85 parts of asphalt. The carbon nanotubes are multi-walled structures with a tube diameter of 12-200nm and a length of 0.5-15μm. The hollow glass microspheres are 30 meshes.

[0085] Preparation method:

[0086] (1) SiO2 aerogel powder and carbon nanotubes were mixed in anhydrous ethanol, the mixed solution was added into a stirrer for stirring, and hollow glass microspheres were added during the stirring process. The stirring temperature was 20°C, the stirring time was 45 minutes, and the stirring speed was 1500 rpm.

[0087] (2) The stirred solution was placed and evaporated at low temperature to precipitate excess ethanol, thereby obtaining a blend of aerogel, carbon nanotubes and hollow glass microspheres. The placement time was 24 hours and the evaporation time was 6 hours at 50°C.

[0088] (3) The dry mixed material was added into an extrusion granulator for granulation, and the particle size was 1 mm.

[0089] (4) The obtained granules were placed in a ball mill for grinding at a speed of 600 rpm for 1 hour, and finally an aerogel composite modifier with a particle size of 60 μm was obtained.

[0090] (5) The asphalt is heated and stirred at a stirring speed of 500 rpm and a stirring temperature of 160° C. for 40 min using a high-speed emulsifying shearing machine, and the aerogel composite modifier is evenly poured into the emulsified asphalt in batches to obtain an aerogel composite modified heat-resistant and heat-insulating asphalt material.

[0091] Example 8

[0092] Example 8 provides a new type of road aerogel insulation layer for areas with large temperature differences, which includes the following raw materials by weight: 13 parts of SiO2 aerogel powder, 1 part of carbon nanotubes, 1 part of hollow glass microspheres, and 85 parts of asphalt. The carbon nanotubes are multi-walled structures with a tube diameter of 12-200nm and a length of 0.5-15μm. The hollow glass microspheres are 30 meshes.

[0093] Preparation method:

[0094] (1) SiO2 aerogel powder and carbon nanotubes are mixed in anhydrous ethanol, the mixed solution is added to a stirrer for stirring, and hollow glass microspheres are added during the stirring process. The stirring temperature is 20°C, the stirring time is 45 minutes, and the stirring speed is 2000 rpm.

[0095] (2) The stirred solution was placed and evaporated at low temperature to precipitate excess ethanol, thereby obtaining a blend of aerogel, carbon nanotubes and hollow glass microspheres. The placement time was 24 hours and the evaporation time was 6 hours at 50°C.

[0096] (3) The dry mixed material was added into an extrusion granulator for granulation, and the particle size was 1 mm.

[0097] (4) The obtained granules were placed in a ball mill for grinding at a speed of 600 rpm for 1 hour, and finally an aerogel composite modifier with a particle size of 50 μm was obtained.

[0098] (5) The asphalt is heated and stirred at a stirring speed of 500 rpm and a stirring temperature of 160° C. for 40 min using a high-speed emulsifying shearing machine, and the aerogel composite modifier is evenly poured into the emulsified asphalt in batches to obtain an aerogel composite modified heat-resistant and heat-insulating asphalt material.

[0099] Example 9

[0100] Example 8 provides a new type of road aerogel insulation layer for areas with large temperature differences, which includes the following raw materials by weight: 13 parts of SiO2 aerogel powder, 1 part of carbon nanotubes, 1 part of hollow glass microspheres, and 85 parts of asphalt. The carbon nanotubes are multi-walled structures with a tube diameter of 12-200nm and a length of 0.5-15μm. The hollow glass microspheres are 30 meshes.

[0101] Preparation method:

[0102] (1) SiO2 aerogel powder and carbon nanotubes were mixed in anhydrous ethanol, the mixed solution was added into a stirrer for stirring, and hollow glass microspheres were added during the stirring process. The stirring temperature was 20°C, the stirring time was 45 minutes, and the stirring speed was 1000 rpm.

[0103] (2) The stirred solution was placed and evaporated at low temperature to precipitate excess ethanol, thereby obtaining a blend of aerogel, carbon nanotubes and hollow glass microspheres. The placement time was 24 hours and the evaporation time was 6 hours at 50°C.

[0104] (3) The dry mixed material was added into an extrusion granulator for granulation, and the particle size was 1 mm.

[0105] (4) The obtained granules were put into a ball mill for grinding. The speed of the ball mill was 600 rpm and the grinding time was 1 hour. Finally, the particle size was 70 μm, which was the aerogel composite modifier.

[0106] (5) The asphalt is heated and stirred at a stirring speed of 500 rpm and a stirring temperature of 160° C. for 40 min using a high-speed emulsifying shearing machine, and the aerogel composite modifier is evenly poured into the emulsified asphalt in batches to obtain an aerogel composite modified heat-resistant and heat-insulating asphalt material.

[0107] Comparative Example 1

[0108] AC-13 asphalt mixture rutting slabs were prepared, and the optimal asphalt-stone ratio was determined to be 4.9%, without adding an aerogel insulation layer.

[0109] In order to verify the effect of the aerogel composite modified heat-resistant and heat-insulating asphalt material provided by the present invention on slowing down the temperature rise of the road surface, four identical 30cm*30cm*5cm AC-13 rutting plates were prepared with reference to the provisions of the highway engineering asphalt and asphalt mixture test procedures, and the aerogel composite modified heat-resistant and heat-insulating asphalt materials of Examples 1-9 were laid on the top and bottom of three rutting plates, respectively, and the 10th plate did not add the aerogel composite modified heat-resistant and heat-insulating asphalt material. Thermocouples were arranged on the upper and lower parts of the four rutting plates, respectively, and heated with an iodine tungsten lamp on the top, simulating the sunlight temperature of 50°C, the heating time was 2h, the initial room temperature was 25°C, and the temperature changes of the upper and lower parts of the rutting plates were measured. The specific test data are shown in Table 1:

[0110] Table 1 Test results of temperature change of rutting plate in high temperature environment

[0111]

[0112] As can be seen from Table 1, the temperature rise of the embodiments of the present invention is significantly different from that of the comparative examples, among which the aerogel effective component in the aerogel composite modifier of embodiment 1 is the highest and the thermal insulation effect is the best. The dosage of embodiments 2 and 3 is lower than that of embodiment 1, so the thermal insulation effect is poor in a high temperature environment, but compared with the comparative example without addition, the cooling range of the bottom temperature is significantly improved.

[0113] By comparing Examples 1, 4, and 5, it can be found that the evaporation time will effectively affect the thermal insulation effect. Among them, by comparing Examples 1 and 5, it can be found that when the evaporation time is increased from 12 h to 24 h, the thermal insulation effect can be effectively improved. This is because increasing the evaporation time helps the aerogel composite modifier to be completely evaporated. However, by comparing Examples 1 and 4, it can be found that the thermal insulation effect is not significantly improved when the evaporation time is increased from 24 h to 36 h. This is because 24 h is sufficient to evaporate the aerogel composite modifier.

[0114] At the same time, by comparing Examples 1, 6, and 7, it can be seen that during the preparation of the aerogel composite modifier, its preparation speed can effectively affect the preparation effect. By comparing Examples 1 and 7, it can be seen that when the preparation speed is increased from 1000 rpm to 2000 rpm, the thermal insulation effect of the aerogel composite modifier is significantly improved, while by comparing Examples 1 and 6, when the speed is increased from 2000 rpm to 3000 rpm, the speed increase is not obvious. This is because the various components of the composite modifier can be evenly distributed at a certain speed, and further increasing the stirring rate after it has been fully stirred will not significantly improve.

[0115] By comparing Examples 1, 8, and 9, it can be found that controlling the final particle size can effectively improve the thermal insulation effect of the aerogel composite modifier on the pavement structure. This is because under the same dosage, reducing the particle size of the modifier particles can effectively increase its distribution density in the pavement structure, help it form a layered system, and improve its thermal insulation effect.

[0116] In order to verify the effect of the aerogel insulation layer provided by the present invention in slowing down the cooling of the road surface, four identical 30cm*30cm*5cm AC-13 rutting plates were prepared with reference to the provisions of the highway engineering asphalt and asphalt mixture test procedures, and the aerogel insulation layer of Examples 1-9 was laid on the top and bottom of 10 rutting plates respectively, and the fourth plate did not add aerogel composite modified heat-insulating asphalt material. Thermocouples were arranged on the upper and lower parts of the 10 rutting plates, respectively, and the temperature of the high and low temperature test box was set to -5°C, the initial room temperature was 25°C, and it was placed in the environmental box from room temperature for 2h, and the temperature changes of the upper and lower parts of the rutting plates were measured. The specific test data are shown in Table 2:

[0117] Table 2 Test results of temperature change of rutting plate in low temperature environment

[0118]

[0119] As can be seen from Table 2, the bottom surface temperature of the three embodiments changes significantly compared with the control example. Among them, as the aerogel content of embodiments 1-3 decreases, the effect of heat preservation and delaying the temperature drop of the pavement structure gradually weakens. At the same time, by comparing embodiments 1, 4, 5, embodiments 1, 6, 7 and embodiments 1, 8, 9 respectively, we can get the effects similar to those in the temperature rise test. This is because the three points of preparation speed, evaporation time and preparation particle size directly affect the effective ingredient content of the modifier and the distribution of the modifier inside the asphalt pavement structure in the preparation process, thereby indirectly affecting the thermal insulation effect of the aerogel composite modified asphalt pavement.

[0120] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0121] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. An aerogel composite modified heat-resistant and heat-insulating asphalt material, characterized in that: In parts by mass, it includes the following components: 8-15 parts of SiO2 aerogel powder; 1-4 parts of carbon nanotubes; 1-3 parts of hollow glass microspheres; 80-85 parts of asphalt; SiO2 aerogel powder, carbon nanotubes and hollow glass microspheres constitute an aerogel composite modifier; In the aerogel composite modified heat-resistant and temperature-insulating asphalt material, the content of the aerogel composite modifier is 15%-20%.

2. The aerogel composite modified heat-resistant and temperature-insulating asphalt material according to claim 1, characterized in that: The carbon nanotubes are multi-walled carbon nanotubes.

3. The aerogel composite modified heat-resistant and temperature-insulating asphalt material according to claim 1, characterized in that: The particle size of SiO2 aerogel powder ranges from 0.1 to 5 mm, and the specific surface area is 800 to 1000 m2 / g.

4. The aerogel composite modified heat-resistant and temperature-insulating asphalt material according to claim 1, characterized in that: The carbon nanotubes have a diameter of 12-200 nm and a length of 0.5-15 μm.

5. The method for preparing the aerogel composite modified heat-resistant and temperature-insulating asphalt material according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) mixing SiO2 aerogel powder, carbon nanotubes and an organic solvent, and adding hollow glass microspheres during the stirring process to obtain a mixed solution; (2) drying the mixed solution to obtain a blend of aerogel and carbon nanotubes; (3) subjecting the blend to high temperature treatment to obtain a dry mixed material; (4) granulating and grinding the dry mixed material to obtain an aerogel composite modifier; (5) Heating the asphalt and performing shear stirring, and then mixing the emulsified asphalt with the aerogel composite modifier to obtain an aerogel composite modified heat-resistant and temperature-insulating asphalt material.

6. The preparation method according to claim 5, characterized in that: In step (1), the stirring temperature is 20-40° C., the stirring time is 30-45 min, and the stirring speed is 1000-3000 rpm.

7. The preparation method according to claim 5, characterized in that: In step (2), the mixed solution is dried, specifically: The mixed solution is placed and evaporated at low temperature, the placing time is 24±1h, and the low temperature evaporation is carried out at 50°C for 6±1h.

8. The preparation method according to claim 5, characterized in that: Step (4) specifically comprises: granulating the dry mixed material to obtain a material with an initial particle size; Grinding the initial particle size material to obtain an aerogel composite modifier; The particle size of the initial particle size material is in the millimeter order; the particle size of the aerogel composite modifier is in the micron order.

9. The preparation method according to claim 5, characterized in that: In step (5), the emulsified asphalt and the aerogel composite modifier are mixed and stirred at a stirring speed of 300 to 500 rpm, a stirring temperature of 140 to 160° C., and a stirring time of 30 to 45 min.

10. The use of the aerogel composite modified heat-resistant and heat-insulating asphalt material according to any one of claims 1 to 4 as a heat-insulating layer in an asphalt pavement, characterized in that: Used as the upper layer of asphalt pavement structure.